An Effective Substitution Technique for Data Hiding in Compressed Video Streams - Vimala, C; Aruna Priya, P (International Journal of Engineering and Technology, 2018)
Data hiding approach is enforced to the encrypted videos for the intent of content notation and tamper detection. Such as, data hiding favored in encrypted domain without decryption extract of the classified content. TheÂ  substitution techniques is used to data hiding in the compressed video. A video file size is closely maintained even after data encryption and embeds. In this work the data has been restored without any loss with better bit rates, Peak Signal Noise Ratio and testify the feasibility and efficiency of the prospective scheme.Â Â